Business Strategy Development in Healthy Food and Drink Business (Case Study: Overjoyed Indonesia) - Utami Putri, Fitri; Hamsal, Mohammad (The Indonesian Journal of Business Administration, 2017)
Abstract. Increase of non-communicable diseases in Indonesia made people in urban areas such as Jakarta has made changes their lifestyle. They chose to eat healthy foods that have benefits for the body. Seeing this opportunity, Overjoyed  establish a business that provides food and drink to support health such as smoothies, pressed juices, and overnight oatmeals. Overjoyed established in early September 2014 and using the concept of product delivery services so that buyers can enjoy the products directly from the office or home. As a newcomer in the food and beverage industry, Overjoyed start promoting their products by doing some marketing activities, but the  brand awareness of Overjoyed is still low. Overjoyed products still do not get the attention of customers. It can be seen from the fluctuations in product sales and sales were below the targets set by the company. To faces the business constraints,, formulating strategies begins by analyzing the internal and external company using Value Chain Analysis, VRIO Framework, PEST Analysis, Porter’s Five Forces, and Competitors Analysis. The results of this analysis will give a conclusion in the form of a SWOT which explains the strengths, weaknesses, opportunities and threats for Overjoyed. Subsequent analysis using TOWS matrix to obtain new ideas and new strategies that will be developed into a new business model canvas. The analysis showed that Overjoyed  have weak brand position when compared with other competitors. Overjoyed conduct marketing activities only once and is not done regularly and continuously. This makes the marketing activities undertaken by Overjoyed less effective. in addition, during production, Overjoyed never replace the variety of flavors on the menu so many customers who leave the product of Overjoyed because they feel bored. The new strategy resulting from the analysis of this study was Overjoyed has to make product innovation, hiring marketing team, make product sales promotion, partnership with delivery company, and so fort. Keywords: Healthy Food and Beverages, Business Strategy, Business Model Canvas Abstract. Increase of non-communicable diseases in Indonesia made people in urban areas such as Jakarta has made changes their lifestyle. They chose to eat healthy foods that have benefits for the body. Seeing this opportunity, Overjoyed  establish a business that provides food and drink to support health such as smoothies, pressed juices, and overnight oatmeals. Overjoyed established in early September 2014 and using the concept of product delivery services so that buyers can enjoy the products directly from the office or home. As a newcomer in the food and beverage industry, Overjoyed start promoting their products by doing some marketing activities, but the  brand awareness of Overjoyed is still low. Overjoyed products still do not get the attention of customers. It can be seen from the fluctuations in product sales and sales were below the targets set by the company. To faces the business constraints,, formulating strategies begins by analyzing the internal and external company using Value Chain Analysis, VRIO Framework, PEST Analysis, Porter’s Five Forces, and Competitors Analysis. The results of this analysis will give a conclusion in the form of a SWOT which explains the strengths, weaknesses, opportunities and threats for Overjoyed. Subsequent analysis using TOWS matrix to obtain new ideas and new strategies that will be developed into a new business model canvas. The analysis showed that Overjoyed  have weak brand position when compared with other competitors. Overjoyed conduct marketing activities only once and is not done regularly and continuously. This makes the marketing activities undertaken by Overjoyed less effective. in addition, during production, Overjoyed never replace the variety of flavors on the menu so many customers who leave the product of Overjoyed because they feel bored. The new strategy resulting from the analysis of this study was Overjoyed has to make product innovation, hiring marketing team, make product sales promotion, partnership with delivery company, and so fort. Keywords: Healthy Food and Beverages, Business Strategy, Business Model Canvas